Canonical orbits for rapidly deforming planar microswimmers in shear ﬂow - Gaffney, EA; Dalwadi, M; Moreau, C; Ishimoto, K; Walker, B (American Physical Society, 2022)
Classically, the rotation of ellipsoids in shear Stokes flow is captured by Jeffery’s orbits. Here, we demonstrate that Jeffery’s orbits also describe high-frequency shape-deforming swimmers moving in the plane of a shear flow, employing only basic properties of Stokes flow and a multiple-scales asymptotic analysis. In doing so, we support the use of these simple models for capturing shapechanging swimmer dynamics in studies of active matter and highlight the ubiquity of ellipsoid-like dynamics in complex systems. This result is robust to weakly confounding effects, such as distant boundaries, and also applies in the low-frequency limit.